PERBANDINGAN KEPEMILIKAN SRS DENGAN APARTEMEN UNTUK ORANG ASING DI INDONESIA DAN THAILAND - Intan Monika; Dinda Keumala (Reformasi Hukum Trisakti, 2021)
High population growth is the reason people choose to live in vertical housing because land in big cities is increasingly limited and land prices are getting higher. The large number of foreign workers in Indonesia also adds to the density of housing in big cities. The problem formulation is the ownership similarity of flats and apartments for foreigners in Indonesia and Thailand, what are the differences in ownership of flats with ownership of apartments for foreigners in Indonesia and Thailand, what causes similarities and differences in ownership of flats with ownership of apartments for foreigners in Indonesia and Thailand. Normative juridical research method, descriptive research nature, conclusion drawing using deductive logic. The results of the research, discussion and conclusions, similarities: land ownership, both countries prohibit foreigners from owning land; The difference: the term mentioning the unit, Indonesia uses the unit of flats and Thailand uses the term of Apartment; quota limit of unit ownership, Thailand regulates foreigners may not own apartments more than 49% of the total units while Indonesia is not regulated. The cause of the similarities between the two countries is the increasing demand for residential needs for foreigners.